Sistem Informasi Administrasi pada Puskesmas Watu Kawula - Arnoldus Ngongo; Herman Huki Ratu; Dian Fransiska Ledi (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
The Watu Kawula Health Center is one of the first level health service facilities that has an important role in providing health services to the community. However, in the implementation of administration, various obstacles are still found such as manual patient data recording, slow service data collection process, and difficulties in reporting and searching data. To overcome these problems, a computerized administrative information system is needed to improve efficiency and accuracy in data management.This research aims to design and build an integrated administrative information system at the Watu Kawula Health Center. The system development method used is the Waterfall model, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The system is designed using the MySQL database and PHP programming language, and is accessed through a web-based interface.The results of the development of the system show that this administrative information system is able to speed up the process of recording patient data, medical services, and making routine reports. In addition, the system also makes it easier for administrative officers to manage information in a structured and systematic manner. With this system, it is hoped that administrative services at the Watu Kawula Health Center can run more effectively and efficiently.